Microbial Halogenation With Specific Reference to Chiloroperoxidase - D.C Smith; A. T Bult; G Holt; C Christy; M. D Lilly; C Rice (ASEAN Journal on Science and Technology for Development, 1987)
Microbial Halogenation With Specific Reference to Chiloroperoxidase